IF THEY FINANCE YOUR CLAIM, WILL THEY PAY ME IF I WIN: IMPLICATIONS OF THIRD PARTY FUNDING ON ADVERSE COSTS AWARDS IN INTERNATIONAL ARBITRATION - Galagan, Dmytro; Živković, Patricia (European Scientific Journal, ESJ, 2015)
Third party funding is a new industry which provides financial support to parties in litigation and arbitration proceedings. The full variety of its implications on international commercial arbitration is yet to be seen. For that reason national courts, arbitral tribunals and doctrine are widely dealing with its repercussions on arbitration proceedings. In order to contribute to this wide discussion, this paper focuses on one particular aspect within the arbitration proceedings influenced by a third party funding: responsibility for payment of adverse costs in cases involving impecunious claimants. The problem presented in this paper is whether, in case where the claimant cannot cover the costs, the third party funder should be responsible for the successful adverse party’s costs, and on which legal basis? The two parts of the paper analyze the possibilities for such funder’s responsibility at two stages of the proceedings: (1) at the stage of a final award and (2) during the proceedings when the security for costs may be sought. The analysis encompasses the court practice and national arbitration laws from several jurisdictions (the United States, the United Kingdom and Germany), the arbitration rules of two leading arbitration institutions (ICC Rules, LCIA Rules), as well as arbitral practice, in order to predict possible issues and illustrate available solutions.